Pengaruh Kepemimpinan Etis dan Keterampilan Komunikasi Terhadap Kinerja Pegawai dengan Motivasi Sebagai Variabel Mediasi dada Inspektorat Daerah Provinsi Sulawesi Tengggara - Eka Astiti Kumalasari; Abd Azis Muthalib; Muh Nur (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this study is to analyze the influence of ethical leadership variables and communication skills on performance variables through motivation as a mediating variable. The types and sources of data in this study are in the form of primary data obtained through questionnaire techniques or distributing questionnaires to all civil servants of the Regional Inspectorate of Southeast Sulawesi Province. While secondary data, namely data obtained through literature studies by referring to literature, journals and various other information related to the problem under study. The data collection method to be used in this study is filling out questionnaires. The data analysis technique is Quantitative data analysis using the SEM-PLS 3 application. The results of hypothesis testing concluded that ethical leadership has no effect on performance, but the variable ethical leadership has a significant positive effect on motivation. The communication skills variable has a significant positive effect on performance and the communication skills variable has a significant positive effect on motivation. The motivation variable can mediate the influence of ethical leadership on performance and the motivation variable is able to mediate the influence of communication skills on performance